The Relationship Between Attitude and Halal Awareness among Food Riders in Batu Pahat - Jul, Siti Noraini; Wan Ahmad, Wan Karimah (Research in Management of Technology and Business, 2025)
This study investigates the relationship between halal awareness and the attitudes of food riders in food delivery services. With the growing demand for halal food options worldwide, particularly among Muslim consumers, the delivery of halal-certified meals has become increasingly important. Food delivery riders play a crucial role in ensuring the timely and safe delivery of food, including halal meals, to customers. However, little is known about how food riders perceive and handle halal food delivery. This research aims to fill this gap by examining the level of halal awareness among food riders and how it influences their attitudes towards halal food delivery services. The researcher has decided to conduct the survey at Batu Pahat. The target population of respondents for this study is inbound food riders. The findings of this study indicate a high level of halal awareness (mean = 4.248, SD = 0.919) and positive attitudes toward halal food delivery (mean = 4.258, SD = 0.902) among food delivery riders in Batu Pahat. A quantitative survey method was utilized, and reliability was confirmed with Cronbach’s alpha values demonstrating good internal consistency for both variables. A strong positive correlation (r = 0.870, p < 0.001) was observed between halal awareness and attitudes, showing that increased awareness significantly enhances adherence to halal principles. These results offer valuable insights for food delivery platforms, policymakers, and other stakeholders, highlighting the importance of implementing halal education and training programs to strengthen compliance, improve service quality, and enhance customer satisfaction in halal food delivery services.